MENGUKUR KINERJA BANK JAMBI SEBELUM DAN SAAT PANDEMI COVID-19 - Fathimah Alfia Rizqi; Yetty Murni; Eka Sudarmaji (Fakultas Ekonomi dan Bisnis Universitas Pancasila, 2022)
The purpose of this study was to analyze the effect of banking ratios, specifically Capital Adequacy Ratio (CAR), BOPO, Net Interest Margin (NIM), Loan to Deposit Ratio (LDR), Non-Performing Loan (NPL), Quick Ratio (QR), Investing Policy Ratio (IPR), GWM, Primary Ratio (PR), Cost of Fund (COF) on financial performance (ROA) at Bank Jambi for the period 2012-2020. The data analysis used linear regression. Normality test, classical assumption test, autocorrelation test, heteroscedasticity test, and multicollinearity test had been performed. The prediction of optimal banking performance ratio based on the coefficient of determination used the Stepwise regression method. The goal of the stepwise regression method was to get the best model from a regression analysis with a high and significant correlation to the dependent variable. If there were variables that were not significant, then the variable was eliminated. This study indicates that only one variable can explain its effect on ROA of the ten independent variables, and the most dominant is the BOPO variable with an R Square value of 0.86 or 86%. Keyword: Financial ratio, Bank JAMBI, Covid19, BOPO, Return On Asset